Identification of Trans-4-Hydroxy-L-Proline as a Compatible Solute and Its Biosynthesis and Molecular Characterization in Halobacillus halophilus - Kim, Kyung Hyun; Jia, Baolei; Jeon, Che Ok (Frontiers in Microbiology, 2017)
Halobacillus halophilus, a moderately halophilic bacterium, accumulates a variety of compatible solutes including glycine betaine, glutamate, glutamine, proline, and ectoine to cope with osmotic stress. Non-targeted analysis of intracellular organic compounds using 1H-NMR showed that a large amount of trans-4-hydroxy-L-proline (Hyp), which has not been reported as a compatible solute in H. halophilus, was accumulated in response to high NaCl salinity, suggesting that Hyp may be an important compatible solute in H. halophilus. Candidate genes encoding proline 4-hydroxylase (PH-4), which hydroxylates L-proline to generate Hyp, were retrieved from the genome of H. halophilus through domain searches based on the sequences of known PH-4 proteins. A gene, HBHAL_RS11735, which was annotated as a multidrug DMT transporter permease in GenBank, was identified as the PH-4 gene through protein expression analysis in E. coli. The PH-4 gene constituted a transcriptional unit with a promoter and a rho-independent terminator, and it was distantly located from the proline biosynthetic gene cluster (pro operon). Transcriptional analysis showed that PH-4 gene expression was NaCl concentration-dependent, and was specifically induced by chloride anion, similar to the pro operon. Accumulation of intracellular Hyp was also observed in other bacteria, suggesting that Hyp may be a widespread compatible solute in halophilic and halotolerant bacteria.